Dakwah Syekh Jangkung Di Palembang: Analisis Komparatif Sumber Sejarah Lokal Dan Jawa - Solimin; Qomarullah, Muhammad; Muklis (Jurnal Khabar: Komunikasi dan Penyiaran Islam, 2025)
This study analyzes the traces of the da'wah of Sheikh Jangkung (Sayyid Raden Syarifuddin) in Palembang by comparing the Javanese hagiography narrative and the local historical context. The background of this research departs from the "Epoch Dilarung" event, where Sheikh Jangkung was exiled by Sunan Kudus for showing unpurified magic, which then led him stranded in Sumatra. The purpose of this study is to dissect the differences in Sheikh Jangkung's da'wah methodology between the Palembang and Java regions and see how Palembang functions as a space for the validation of his spiritual authority. The research method used is descriptive qualitative with a comparative analysis approach of historical sources, which includes the manuscript of Ihtisar Riwayat Syeh Jangkung, Serat Syekh Jangkung (SSJ), as well as oral traditions and Ketoprak performances. The results of the study show that Sheikh Jangkung's da'wah in Palembang is dominated by the Istisyfa (healing) method through karomah demonstrations to overcome disease outbreaks (pagebluk) and the Sultanate's political crisis. This is in stark contrast to da'wah in the Javanese agrarian environment (Pati) which uses the Irsyad Da'wah method through the example of morality and long-term social ethics. His success in Palembang resulted in political legitimacy in the form of marriage to the Sultan's daughter and the division of territory, which theologically validated the transformation of "sacredness" into "karomah" before he returned to Java with full spiritual authority.